The Effect of Total Assets, Earning Management and Debt to Equity Ratio on Return on Investment in Infrastructure, Utility and Transportation Companies Listed in Indonesia Stock Exchange 2012-2015 Period - Thomas Firdaus Hutahaean (Journal of Business, Management, & Accounting, 2020)
The objective of the study was to examine and analyze the effect of total asset turnover, earnings management and debt to equity ratio on Return on Investment in listed in the Indonesia Stock Exchange Infrastructure, Utility and Transportation Companies in the period of 2012-2015. The research approach used is quantitative analysis. This type of research is quantitative descriptive research. The study population was the Financial Statements of 46 Infrastructure, Utility and Transportation Companies which the Indonesia Stock Exchange in the period of 2012-2015. The sample of this study were 8 Infrastructure, Utility and Transportation Companies. Before the regression model is used to test hypotheses, the model has been previously tested for classical assumptions. Classical assumption tests are carried out include: autocorrelation test, heteroscedasticity test, and multicollinearity test. The test results that become the conclusion of this study stated that total assets turnover was not significantly affect Return on Investment in the Indonesian Stock Exchange in the period of 2012-2015 in Infrastructure, Utility and Transportation Companies. Earnings management had a significant effect on Return on Investment on Infrastructure, Utility and Transportation Company of the Indonesia Stock Exchange in the period of 2012-2015. Debt to equity ratio has no significant effect on the Return on Investment of the Indonesian Stock Exchange in the period of 2012-2015. Total asset turnover, earnings management and debt to equity ratio have a significant and significant impact on the Return on Investment of the Indonesia Stock Exchange in the period of 2012-2015 Infrastructure, Utility and Transportation Companies.